[Situation actuelle de l'identification électronique chez les ovins et caprins à l'aide de transponders passifs] - Caja G.; Nehring R.; Conill C.; Ribo O.; Peris S.; Solanes D.; Barillet F.; Marie C.; Ricard E.; Aurel M.R.; Jacquin M.; Lagriffoul G. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
Injectable, electronic ear-tags and ruminal bolus transponders are the devices used in sheep and goat electronic identification in practice and are reviewed in this paper. Injectable transponders are embodied into a bio-compatible glass capsule and are injected subcutaneously into the animals' body. The main problems observed are losses, breakages and recovery after slaughter. In relation to the injection body site, only the armpit and ear-base are recommended for sheep in field conditions. The armpit was also recommended for subcutaneous injections in goats. Electronic ear-tags are at present applied in dairy sheep or dairy goat farms for automatic feeding of concentrates. The ear-tag weight must be limited when it is applied in young animals, reducing its reading distance and dynamic reading efficiency in consequence. The main advantages of ear-tags are related to its easy recovery and reutilisation in the farm. The use of a ruminal ceramic bolus has been proposed to be used indistinctly in sheep, goat and cattle at different ages. Oral administration of bolus is easy and safe, but the application in animals heavier than 25 kg is only recommended in practice. No negative reaction or behaviour alteration were observed in any animal after bolus administration. No losses, breakages or failures were observed one year after application in grazing or semi-stabled sheep and goat and reading efficiency in restrained and in moving animals walking through a race-way was 100 per cent. Two comparative trials using electronic ear-tags, injectable and ruminal bolus transponders carried out in two experimental dairy sheep farms, are also discussed.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)